Absence of socioeconomic inequalities in access to good-quality breast cancer treatment within a population-wide screening programme in Turin (Italy). Issue 6 (November 2016) - Zengarini, Nicolás; Ponti, Antonio; Tomatis, Mariano; Casella, Denise; Giordano, Livia; Mano, Maria P.; Segnan, Nereo; Whitehead, Margaret; Costa, Giuseppe; Spadea, Teresa
Abstract : Several studies suggest that population-based breast cancer screening programmes might help reduce social inequalities in breast cancer survival both by increasing early diagnosis and by improving access to effective treatments. To start disentangling the two effects, we evaluated social inequalities in quality of treatment of screen-detected breast cancer in the city of Turin (Italy). Combining data from the Audit System on Quality of Breast Cancer Treatment and the Turin Longitudinal Study, we analysed 2700 cases in the screening target age class 50–69 diagnosed in the period 1995–2008. We selected 10 indicators of the pathway of care, relative to timeliness and appropriateness of diagnosis and treatment, and three indicators of socioeconomic position: education, occupational status and housing characteristics. For each indicator of care, relative risks of failure were estimated by robust Poisson regression models, controlling for calendar period of diagnosis, size of tumour and activity volume of the surgery units. The principal predictor of failure of the good care indicators was the calendar period of diagnosis, with a general improvement with time in the quality of diagnosis and treatment, followed by size of the tumour and volume of activity. Socioeconomic indicators show only a marginal independent effect on timeliness indicators. The observed associations of quality indicators with socioeconomic characteristics are lower than expected, suggesting a possible role of the screening programme in reducing disparities in the access to good-quality treatments thanks to its capability to enter screen-detected women into a protected pathway of care.